Destruction properties of grading materials used in the martial arts - Ackland, T.; Paterson, C. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Common materials used for "breaking" in martial arts were subjected to static load tests using an Instron 8501 machine. The test materials, including "Radiata" pine boards and ceramic roofing tiles, demonstrated significant variability (.30%) in peak yield force during static load-to-failure tests. Individual force-time histories demonstrated that each board had a linear elastic region and no plastic region prior to the yield point. Though still essentially linear, the elastic region for ceramic tiles was less regular, but still revealed a definitive yield point. Furthermore, such factors as grain structure, applied force position, orientation, and material size and age were shown to affect the destruction properties.